Konstruowanie wzajemnych relacji jako element stylu uprawiania polityki PO i PiS - Marzęcki, Radosław (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The subject of this paper is an analysis of behavior on the Polish political stage. Its starting point is a reflection on conflict and consensus in a democratic system. This general context requires us to approach these phenomena in terms of a range of aspects which can in turn affect the final assessment of conflict and consensus from the point of view of the quality of the political system. It turns out that the most important communication channels for this interaction are systematically and consistently closed by both sides involved in the conflict. The assumption that this political activity is inspired by marketing suggests that such a strategy has been planned in advance and is rationally implemented.